Analisis Pertumbuhan Iman Katakumen Dewasa Stasi St. Yohanes Gabriel Perboyre Surabaya Angkatan Tahun 2023-2024 (Tinjauan Manajemen Operasional) - Christian, Stefanus Lumen; Esti, Christina (Felicitas, 2024)
Every people have the free will to hold certain beliefs. If someone wants to become a Catholic, he must become a catechumen firstly till he receive the Sacrament of Baptism. A catechumen will learn about the teachings of the Catholic Church through the catechumenate process. This process also grows faith when he begins to practice it in every life. In addition, the faith growth of catechumen is related to the results of a comprehensive interaction between inputs; process; and output, namely through the pre-catechumenate, catechumenate, and the Sacrament of Baptism. In operational management, the faith growth of catechumen shows that learning about the Catholic Church creates Christian values within them. This is because there is a transformation process in their respective lives, where initially they have different belief backgrounds (input) until finally they receive the Sacrament of Baptism and are welcomed as part of the Catholic Church (output). This article will show the results of the analysis regarding the faith growth of catechumen in St. John Gabriel Perboyre Surabaya Station class of 2023-2024 reviewed through operational management (input; process; and output).